Our experience in parenteral feeding - Cid, Alberto; Verderosa, Walter; Rodrigo, Carlos; Arismendi, Angel; Baccino, Luis E; Rey, Néstor; Medina, Mario; Pedezert, María L; Goitía, Sonia; Franca, Olga (Cirugía del Uruguay, 1975)
A description is given of the experience acquired in an Intensive Care Unit, wbere the techniques of Parenteral Feeding were employed in 15 patients witb serious surgical illness, in state of catabolism, during periods from 6 to 72 days. This was acomplished by infusion througb a central venous catheter of a 30 % glucose solution (to provide calories) and crystalline L-amynoacid solution (to provide nitrogen). This latter constitutes a variation from the original Dudrick procedure. The caloric/nitrogen relation fluctuated between 188 and 458, and the potassium/nitrogen relation was between 5 and 1 7. The administration of vitamins, minerals and oligo-elements, completed the technique. In all the cases studied, an inversion of the nitrogenous balance to the pbase of anabolism was obtained, with increase of weigbt, accompanied by general subjective improvement. The most frequent complication was transient hyperglycemia, that eventually required insulin. Attention is called to the importance of excellent clinical and laboratory controls to avoid metabolic or ionic disturbances and septical complications, specially those by gram-negative bacteria or fungi.